'Comandante Honorofico das FAPLA' Alexei Ivanovich Dubenko. Issue 1 (2nd January 2022) - Shubin, Vladimir
ABSTRACT 1 : This 2 short research note provides an outline of and some details on the military service of Soviet naval officer Alexei Ivanovich Dubenko from the perspective of his colleague Vladimir Shubin. For much of his career, Dubenko served in Africa liaising with African national liberation movements and governments friendly toward the Soviet Union. It pays particular attention to his service in Angola, during which Angola's MPLA government awarded him the title of 'Honourary Comandante of FAPLA' — the highest rank in the armed forces of Angola.